2019
DOI: 10.1002/ange.201903539
|View full text |Cite
|
Sign up to set email alerts
|

Von Polyhalogeniden zu Polypseudohalogeniden: Chemie basierend auf Bromcyan

Abstract: Pseudohalogene sind molekulare Einheiten mit ähnlichen chemischen Eigenschaften wie die der Halogene. Während unser Verständnis der Polyhalogenchemie in den letzten Jahren zugenommen hat, ist die Forschunga nP olypseudohalogenverbindungen deutlich weniger entwickelt. Das Pseudohalogen BrCN besitzt ein stark ausgeprägtes,b romzentriertes s-Loch, das die Ausbildung starker Halogenbrücken fçrdert. Dies ermçglicht die Synthese und Charakterisierung neuer Polypseudohalogenanionen, wie die Einkristall-Rçntgenstruktu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The reaction of bromide salts with over-stoichiometric amountso fH Br leads to the formation of rather instable compounds which could not be characterizedw hile the reactiono f Recently it was shown that BrCN forms adducts with bromide to form [Br(BrCN) n ] À anions (n = 1, 3) by halogen bonding interactions. [32] Therefore it was tested whether similar hydrogen-bonded compounds can be synthesized. [ PPN][Br(HCN)] was obtained by the reactiono f[ PPN]Br with four equivalents of HCN.…”
Section: Furtherinvestigations On Hydrogen Bonddonors and Acceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of bromide salts with over-stoichiometric amountso fH Br leads to the formation of rather instable compounds which could not be characterizedw hile the reactiono f Recently it was shown that BrCN forms adducts with bromide to form [Br(BrCN) n ] À anions (n = 1, 3) by halogen bonding interactions. [32] Therefore it was tested whether similar hydrogen-bonded compounds can be synthesized. [ PPN][Br(HCN)] was obtained by the reactiono f[ PPN]Br with four equivalents of HCN.…”
Section: Furtherinvestigations On Hydrogen Bonddonors and Acceptorsmentioning
confidence: 99%
“…All observed bands are significantly shiftedt ol ower wavenumbersc ompared to crystalline HCl at 2705a nd 2748 cm À1 (measured at À196 8C) [29] which indicates hydrogen bond interactions.Three major trends can be emphasized in the recorded Ramans pectra: [30] [Cl(BrCl) 6 ] À [31] and [Br(BrCN) 3 ] À . [32] Therefore ]n ob ands are observed in the HCl stretchingr egion which might be due to the low intensity of these bands (Figure S17).…”
Section: Introductionmentioning
confidence: 99%